Types of nasal deformities in individuals seeking rhinoplasty at governmental hospital in Saudi Arabia - Alotaibi, Abdullah D.; Alsuwayt, Bashayr N.; Raghib, Rana N.; Alsayer, Rahaf S.; Albarrak, Sarah M.; Alrasheedi, Abdullah N.; Saleem, Mohd; Afreen, Sheeba; Friedman, Oren (Frontiers in Surgery, 2024)
IntroductionThis study explores the profound impact of nasal structure on individuals' self-image and emotional well-being, emphasizing the increasing popularity of rhinoplasty in Saudi Arabia, influenced by societal beauty standards portrayed on social media. The investigation aims to unravel the complex interplay between demographic factors, such as gender and age distribution, and prevalent nasal deformities in a cohort of 293 participants.Material and methodsThis retrospective study at the University of Hail and King Khalid Hospital, Saudi Arabia, investigated nasal deformities in 293 participants aged 15–54. Ethical approval was obtained, and data, including bio-demographics and nasal deformities, were retrospectively reviewed. Statistical analyses, utilizing chi-square and Fisher exact tests, assessed associations, enhancing internal validity. The study targeted a diverse population, emphasizing ethical guidelines and systematic sampling.ResultsOur study of 293 participants revealed a prevalence of common nasal deformities. Dorsal hump deformity (59.0%) was the most prevalent, followed by external nasal deviation (54.6%). Significant gender differences were observed, with males more prone to external nasal deviation (65.6%), while decreased nasal tip rotation was more common in females (40.6%). Variations in nasal tip shape were statistically significant, with broad nasal tip shape more prevalent in females (35.2%).ConclusionIn conclusion, our study highlights the prevalence of common nasal deformities, emphasizing significant gender variations. These findings contribute to a deeper understanding of nasal anatomy, essential for informed decision-making in rhinoplasty.